A step in a new direction: The effect of the parent's money reform of 2007 on employment rates of mothers in Germany - Susanne Schmidt (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Increasing maternal employment rates engage policies and people for decades. It is pushed but also questioned at the same time depending on whether women are regarded in first line as mothers or workers. In Germany, the male breadwinner model is traditionally favored. The parent's money reform of 2007 is regarded as a first step towards the dual earner - dual carer model by some scholars. Compared to previous reform, it introduced a shorter time span of receiving a child-raising benefit, a higher benefit and two additional months extending the reference period if both parents participate in child raising. This paper addresses the question what is the effect of the parent's money reform of 2007 on maternal employment rates? Using the SOEP, an ex-post impact evaluation with difference-in-difference estimator and propensity score matching is done to investigate causal effects of the reform on the employment rates of mothers. The results reveal that the mothers giving birth under the new reform start significantly earlier working than mothers bearing a child under the old reform, but the number of working mothers did not increase. This observation results in the conclusion that the parent's money reform did not fulfill its role as a driver towards a shift the dual earner - dual carer model. Future policies should have an explicit holistic approach to improve the reconciliation of work and family life.
Keywords: 330; labor; gender; family and networks